Dream Analysis in the Novel “1984” by George Orwell - Tuychiyevna, Musayeva Dilsuz (European Journal of Life Safety and Stability (2660-9630), 2023)
Since the beginning of time, when humanity’s first predecessors lived, dreams have been acknowledged as an essential component of human life. Our forefathers gave dreams a lot of weight because they believed that they were signs of things to come in their destiny, even though dreams are typically associated with the idea of death and a trip to another realm. In this article, we discuss several dream-related beliefs both before and after applying psychanalytic theory to dream analysis.